2018
DOI: 10.1002/smll.201803156
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Assisted Coil–Globule Transition for Scalable Preparation of Water‐Resistant CsPbBr3@PMMA Perovskite Nanospheres with Application in Live Cell Imaging

Abstract: Despite their impressive optical properties, lead halide perovskite quantum dots (PQDs) have not realized their potential, especially in bioimaging applications, as they suffer from poor moisture and thermal stability, solvent incompatibility, and significant toxicity. Here, a spray‐assisted coil–globule transition method for encapsulating CsPbBr3 (CPB) PQDs into poly(methyl methacrylate) (PMMA) polymer nanospheres is reported. Polyvinylpyrrolidone‐capped CPB PQDs are synthesized via the ligand assisted reprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 51 publications
2
106
0
Order By: Relevance
“…CsPbBr 3 QDs have no significant aggregation in the SiO 2 matrix, and the dispersion is better. It should be noted that the particles are easily aggregated if CsPbBr 3 PQDs are used directly in the post‐processing step without the protection of PS . CsPbBr 3 QDs/silica composites have a lattice distance of 0.412 nm, corresponding to the (1 1 0) crystal plane of the cubic phase perovskite (Figure d and the inset), suggesting that silica encapsulation preserves the size and structure of CsPbBr 3 QDs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…CsPbBr 3 QDs have no significant aggregation in the SiO 2 matrix, and the dispersion is better. It should be noted that the particles are easily aggregated if CsPbBr 3 PQDs are used directly in the post‐processing step without the protection of PS . CsPbBr 3 QDs/silica composites have a lattice distance of 0.412 nm, corresponding to the (1 1 0) crystal plane of the cubic phase perovskite (Figure d and the inset), suggesting that silica encapsulation preserves the size and structure of CsPbBr 3 QDs.…”
Section: Figurementioning
confidence: 99%
“…It is observed that the average diameter of silica-coated CsPbBr 3 QDs is 8.2 nm, size deviation is 0.1 nm, and there was no significant change before and after coating.C sPbBr 3 QDs have no significant aggregation in the SiO 2 matrix, and the dispersion is better.I t should be noted that the particles are easily aggregated if CsPbBr 3 PQDs are used directly in the post-processing step without the protection of PS. [20] CsPbBr 3 QDs/silica composites have al attice distance of 0.412 nm, corresponding to the (110) crystal plane of the cubic phase perovskite (Figure 2d and the inset),s uggesting that silica encapsulationp reserves the size and structure of CsPbBr 3 QDs. The presenceo fC s, Pb, Br,S i, and Oi nt he CsPbBr 3 QDs/silica composites was confirmed by energy-dispersive X-ray spectroscopy (EDX) mapping (Figure 2e).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, many groups have been devoted to preparing FNs by different methods, such as encapsulating fluorescent molecules or quantum dots into the matrix spheres [16][17][18] and placing nanoparticles on the surface of matrix spheres [19,20]. In consideration of differentiated application environments, FNs are fabricated based on different matrices, including polystyrene [21], polymethyl methacrylate [22], silica [23], polylactic acid [24], melamine formaldehyde [25], sodium alginate [26], conjugated microporous polymers [27] and nanocellulose [28]. Each type of matrix spheres and preparation methods has advantages and disadvantages, with respect to the cost-effectiveness, properties and stability of FNs, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…These excellent attributes make perovskite nanocrystals particularly attractive for applications in fluorescent biotagging or related biotechnologies. Presently, however, their use as biotagging or magneto‐fluorescent agents remain limited primarily due to their instability toward polar solvents, such as water or ethanol, of which are essential in the Stöber process needed for forming an encapsulating silica shell. While there have been reports of works describing the stabilization of perovskite nanoparticles through formation of silica shells via modified Stöber processes, these amorphous and typically porous shells are insufficient in providing protection toward water.…”
mentioning
confidence: 99%